Analisis Implementasi Kebijakan Penanggulangan Stunting di Kota Manado - Melinda Y. Tompunu; Jeanette I. Ch. Manoppo; Margareth R. Sapulete (Pusat Riset dan Inovasi Nasional, 2025)
Stunting is a chronic nutritional problem that has an impact on the quality of human resources and long-term productivity. Manado City as the capital city of North Sulawesi Province still faces challenges in reducing stunting rates. This study aims to analyze the implementation of stunting control policies in Manado City with a focus on specific interventions implemented by the Health Office and Health Centers. The study used a qualitative approach with a descriptive method. Data were collected through in-depth interviews, observations, and documentation of key informants, namely Health Office officials, nutrition management personnel, health cadres, and parents of stunted toddlers. The results of the study showed that communication had run smoothly, but the community's understanding of stunting was still less than ideal. Human resources and facilities were still limited. The disposition of implementers showed high commitment, but the lack of incentives was an obstacle. The bureaucratic structure of stunting control in Manado City was clear through coordination between the Health Office, Health Centers, and health cadres, with the support of SOPs that strengthened implementation in the field. In conclusion, the implementation of stunting control policies in Manado City has not been implemented properly and still requires strengthening in terms of communication, resources, and motivation of implementers.